METHODOLOGY FOR OPTIMIZING DRILL BIT PERFORMANCE - Pashchenko, Oleksandr; Ratov, Boranbay; Khomenko, Volodymyr; Gusmanova, Aigul; Omirzakova, Elmira (International Multidisciplinary Scientific GeoConference SGEM, 2024)
The optimization of technological processes 1s vital for advancing scientific and technical progress in exploration activities, particularly in drilling operations. The integration of operating microprocessor equipment and automated management systems has opened up new opportunities for theoretical research in optimization processes and drillings. Control systems for drilling exploration wells on solid minerals enable realtime operation and data collection, processing, and diagnosis of equipment functionality. Optimization of technological processes using modern equipment aims to enhance production efficiency, improve quality, and reduce costs. Despite advancements in equipment, tools, and drilling technology, there are still significant opportunities for increasing productivity and improving technical and economic indicators in prospecting drilling. Optimization criteria vary depending on the objectives, with the maximum productivity often achieved by minimizing drilling time. The task of finding the maximum drilling speed per run involves optimizing parameters such as weight on bit, tool speed, and mud flow rate. A novel technique proposed in this study involves cyclic intra-run changes in speed per minute as the optimization criterion, rather than mechanical speed. The developed method is applicable to any rock cutting instrument and drilling method, with the optimization of drilling speed per run as a function of drilling time. The use of time and speed coefficients simplifies calculations and reveals regularities in the drilling process, contributing to the optimization of drilling operations.